Invasive Vaucheria aff. compacta (Xanthophyceae) and its distribution over a high Arctic tidal flat in Svalbard. (5th February 2023) - Elster, Josef; Souquieres, Claude-Eric; Jadrná, Iva; Škaloud, Pavel; Søreide, Janne E.; Kvíderová, Jana
Abstract: The high Arctic Svalbard tidal flat ecosystem is impacted by global warming, which could allow invasion by additional species with changes in the environment supporting their growth. The transport of additional species to Svalbard could be aided by an increase in the numbers of people traveling there. Anthropogenic activities related with global warming create opportunities for organisms to move across previously isolated regions, thus advancing biotic homogenization and extinctions. Our study focused on essential quantitative and qualitative information about the occurrence of widespread mats of the invasive siphonaceous yellow-green alga Vaucheria aff. compacta in the Adventfjorden tidal flat. We outline the present ecological state of V. aff. compacta mats (land cover estimation) and discuss the origin and future development of this microphytobenthic community. Phylogenetic analyses based on rbc L genes confirmed that the studied alga is closely related to V. compacta, inside the section Piloboloideae. With the help of a drone mapping survey, we estimated that V. aff. compacta area cover was about ca 231.1 m 2 ( ± 10.55%, n = 11) across the drone mapped tidal flat area of 2475 m 2 . We confirmed that invasive V. aff. compacta is a coastal cosmopolitan species widely disseminated on shores in both hemispheres. Invasive V. aff. compacta is an important component of the Adventforden sea-land ecotone, which affects large-scale changes within the intertidal system, stabilizes the sediment coming in with the regular tides and protect the seashore ecosystem against erosion. As a result of global warming in the Arctic, invasive V. aff. compacta facilitates the greening of the Arctic. Graphical abstract: Image 1 Highlights: Rbc L genes of V. aff. Compacta confirm it is an invasive species in the Svalbard tidal flat. V. aff. Compacta covers about ca 231.1 m 2 ( ± 10.55%, n = 11) across mapped the tidal flat area of 2475 m 2 . V. aff. Compacta is a coastal cosmopolitan species disseminated in both hemispheres.